EDUCATIONAL REVOLUTION IN THE CLASSIC ERA, 650–1250 AD - Rahman, Munawirur; Tobroni, Tobroni; Faridi, Faridi (LP2M IAI Al-Khairat Pamekasan, 2024)
Study This aim is to explore movement education in the future classic that is on period 650–1250 AD on period golden. This is known as the golden period of Islam, with appearance figures revolutionary, especially in education and religion. Besides exploration, also aim for hook with condition day. This has implications. Study This use studies literature from various objective references to evaluate figures revolutionary at the time, namely 650–1250 AD. results study This shows that there are a minimum of five characters who are revolutionary in education, namely Al-Kini, Al-Farabi, Ar-Razi, Ibnu Sina, and Al Kharizmi. In general, Islam developed between 650 and 1250 AD, which can be considered an important period in history knowledge. From the characters revolutionary, they appear to have developed various fields of science, so his work is still very influential at the moment.